Systematic Review and Meta-Analysis of the Y-Balance Test Lower Quarter: Reliability, Discriminant Validity, and Predictive Validity - Phillip Plisky; Katherine Schwartkopf-Phifer; Bethany Huebner; Mary Beth Garner; Garrett Bullock (International Journal of Sports Physical Therapy)
# Background